Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, Với \(x>0;x\ne1\)
\(P=\left(\frac{\sqrt{x}}{2}-\frac{1}{2\sqrt{x}}\right)^2\left(\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{\sqrt{x}+1}{\sqrt{x}-1}\right)\)
\(=\left(\frac{x-1}{2\sqrt{x}}\right)^2\left(\frac{x-2\sqrt{x}+1-x-2\sqrt{x}-1}{x-1}\right)\)
\(=\frac{x^2-2x+1}{4x}.\frac{-4\sqrt{x}}{x-1}=\frac{1-x}{\sqrt{x}}\)
Thay x = 4 => \(\sqrt{x}=2\)vào P ta được :
\(\frac{1-4}{2}=-\frac{3}{2}\)
c, Ta có : \(P< 0\Rightarrow\frac{1-x}{\sqrt{x}}< 0\Rightarrow1-x< 0\)vì \(\sqrt{x}>0\)
\(\Rightarrow-x< -1\Leftrightarrow x>1\)
\(\sqrt{1-x}\left(\sqrt{5-x}-3\right)=0\)
\(\sqrt{5-x}=3\)
\(5-x=9\)
\(x=-4\)
ta có \(\sqrt{\left(x-1\right)\left(x-5\right)}-3\sqrt{1-x}=0\)
\(\Leftrightarrow\sqrt{\left(1-x\right)\left(5-x\right)}-3\sqrt{1-x}=0\)
\(\Leftrightarrow\sqrt{1-x}\left(\sqrt{5-x}-3\right)=0\)
mà x<1=>x khác 1=>\(\sqrt{5-x}-3=0\)
\(\Rightarrow x=-4\)=> \(a^2+a=12\)
Ta có: \(x-3\sqrt{x}+2=0\)
\(\Leftrightarrow\left(\sqrt{x}-2\right)\left(\sqrt{x}-1\right)=0\)
=>x=4 hoặc x=1
Khi x=4 thì \(A=2\cdot\left(1-2\right)=-2\)
Khi x=1 thì \(A=1\cdot\left(1-1\right)=0\)
Nguyễn Lê Phước Thịnh , điều kiện 0<x<1 bn ơi??